Application of a general methodology to understand vulnerability and adaptability of the fisheries for small pelagic species in the Benguela countries: Angola, Namibia and South Africa. Issue 4 (1st October 2020) - Cochrane, KL; Ortega-Cisneros, K; Iitembu, JA; dos Santos, CI; Sauer, WHH
Abstract : The fisheries for small pelagic species in Angola, Namibia and South Africa fulfil important social and economic roles but have undergone substantial changes in recent years, some of which are likely to be related to climate change. This assessment of vulnerability and possible adaptation options for the main stakeholder groups in these fisheries was based on a framework encompassing ecological, social and economic vulnerability and the broader economic and governance context of the countries. Information was gathered through stakeholder consultations and workshops as well as from published information. Adaptation options were identified primarily through consultation with stakeholders. Namibia was considered to have the most vulnerable fishery because of the poor state of the sardine population and limited alternatives. Angola and South Africa were estimated to be moderately vulnerable for different reasons. Alternative sources of livelihoods are scarce, and the wellbeing of stakeholders is highly dependent on the resilience and adaptive capacity of individual fishing companies. For land-based and sea-going workers (fulltime and permanent), skills improvement to increase their flexibility and employability within and beyond fisheries is a primary adaptation option. Key roles for governments include ensuring effective governance and facilitating sustainable economic development, especially in underdeveloped coastal areas.